Powdery mildew fungi (Erysiphales) of Botanical Garden of Odessa National Mechnikov University (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
A list of species of Erysiphales fungi on the territory of Botanical Garden of Mechnikov Odessa National University is studied. 47 species belonging to 8 genera of the order Erysiphales is found as parasites of 152 species, 5 forms and 4 varieties of plants belonging to 118 genera and 37 families. The most species-rich genera are Erysiphe R. Hedw. ex DC. (19 species, 40,4%), Podosphaera Kunze (12 species, 25,5%) and Golovinomyces (U. Braun) Heluta (7 species, 14,9%). This article presents a complete list of powdery mildew fungi.
Keywords: Erysiphales, fungi, host plants, botanical garden.